Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/6679746
|View full text |Cite
|
Sign up to set email alerts
|

Human Motion Gesture Recognition Based on Computer Vision

Abstract: Human motion gesture recognition is the most challenging research direction in the field of computer vision, and it is widely used in human-computer interaction, intelligent monitoring, virtual reality, human behaviour analysis, and other fields. This paper proposes a new type of deep convolutional generation confrontation network to recognize human motion pose. This method uses a deep convolutional stacked hourglass network to accurately extract the location of key joint points on the image. The generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Wenbo et al put forward a protocol recognition method based on CNNs to improve the accuracy of feature acquisition, and it was proved that the proposed algorithm had high accuracy and fast convergence speed [14]. Ma et al proposed a novel deep convolutional generative adversarial network to recognize human action posture, and verified through experiments that its model had significant advantages over existing models [15]. Chen et al put forward a multi-radar collaborative HAR model based on transfer and integrated learning to solve the view limitation in AR.…”
Section: Related Workmentioning
confidence: 99%
“…Wenbo et al put forward a protocol recognition method based on CNNs to improve the accuracy of feature acquisition, and it was proved that the proposed algorithm had high accuracy and fast convergence speed [14]. Ma et al proposed a novel deep convolutional generative adversarial network to recognize human action posture, and verified through experiments that its model had significant advantages over existing models [15]. Chen et al put forward a multi-radar collaborative HAR model based on transfer and integrated learning to solve the view limitation in AR.…”
Section: Related Workmentioning
confidence: 99%
“…Ma et al [ 20 ] suggested a novel deep convolutional generation confrontation network to recognize human motion poses. This method uses a deep convolutional stacked hourglass network to precisely extract the location of key joint points on the image.…”
Section: Related Workmentioning
confidence: 99%
“…Various techniques have been developed for activity recognition, both computer vision-based and sensor-based [2]. Computer vision usage requires a camera device to capture human activities [3,4]. This computer vision technique can provide good results, but lighting, privacy, processing complexity, and fixed camera positions still need to be solved [1,2,6].…”
Section: Introductionmentioning
confidence: 99%